2021
DOI: 10.1111/petr.14088
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in children with HPS: Experience from two high volume liver transplant centers across continents

Abstract: Background: Severe HPS increases morbidity and mortality after LT in children. We reviewed the combined experience of LT for HPS in children from two LT centers in Europe and Asia. Methods: All children with "proven" HPS as per ERS Task Force criteria (detailed in manuscript) who underwent LT were categorized into M (PaO 2 ≥80 mmHg), Mo (PaO 2 = 60-79 mmHg), S (50-59 mmHg), and VS (PaO 2 <50 mmHg) HPS, based on room air PaO 2 .Results: Twenty-four children with HPS underwent 25 LT (one re-transplantation) at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[37] Although there are robust data to support an association between room air oxygenation and posttransplantation survival in adult HPS patients, the largest studies on this topic in children were just recently published and derived from retrospective cohorts of less than 25 patients each. [38,39] The authors observed that although children with very severe HPS (PaO 2 < 50 mm Hg) required longer durations of mechanical ventilation, longer intensive care unit (ICU) and hospital stays, and longer O 2 weaning time than those with mild, moderate, or severe HPS (PaO 2 > 50 mm Hg), there was no difference in mortality across subgroups. Although our findings also indicate that severity of HPS does not impact post-LT survival in children, our analysis expands on the size and depth of this work.…”
Section: Discussionmentioning
confidence: 99%
“…[37] Although there are robust data to support an association between room air oxygenation and posttransplantation survival in adult HPS patients, the largest studies on this topic in children were just recently published and derived from retrospective cohorts of less than 25 patients each. [38,39] The authors observed that although children with very severe HPS (PaO 2 < 50 mm Hg) required longer durations of mechanical ventilation, longer intensive care unit (ICU) and hospital stays, and longer O 2 weaning time than those with mild, moderate, or severe HPS (PaO 2 > 50 mm Hg), there was no difference in mortality across subgroups. Although our findings also indicate that severity of HPS does not impact post-LT survival in children, our analysis expands on the size and depth of this work.…”
Section: Discussionmentioning
confidence: 99%
“…However, these programs are primarily based in the private sector. [5][6][7][8][9] Sri Lanka (SL) is an island nation located in South Asia, next to India geographically. It is categorized as a low-middle income country with a diverse population, comprising various ethnic groups.…”
Section: Introduction/backg Roundmentioning
confidence: 99%
“…India being one of the SA countries is successfully performing a high volume of pediatric liver transplants (PLT) each year, including auxiliary and domino LTs. However, these programs are primarily based in the private sector 5–9 …”
Section: Introduction/backgroundmentioning
confidence: 99%